PROFILE OF STUDENT REPRESENTATION OF ELECTRICAL ENGINEERING AT PHYSICS LECTURE - Ike Festiana (Universitas Nahdlatul Ulama Lampung, 2018)
Representation is very important used in electrical engineering students in physics lectures. Representation consists of verbal, mathematics, diagrams, and graphs. This research uses case study method in electrical engineering students who are physics lectures. Data were collected using questionnaires, observations sheet, and interview guidlines. Based on the questionnaire, the results of the teaching materials used are not yet complete using multi representation, the lecture model does not use multi representation, and the problem is used more using verbal and mathematic representation. Electrical engineering courses are required by using multi representation.